Performance of different rubber tree clones against South American leaf blight (Microcyclus ulei) - Silva, Liliane Gomes da; Jesus Júnior, Waldir Cintra de; Souza, Antonio Fernando; Alves, Fabio Ramos; Furtado, Edson Luiz [UNESP] (Wiley, 2014)
This study was aimed to evaluate the behaviour of eighteen clones of Hevea brasiliensis (rubber) against South American leaf blight and tostudy progress of the disease. The experiment was conducted in Cachoeiro de Itapemirim-ES, where 18 clones were evaluated. The experi-mental design was a randomized block with four replicates; each experimental unit consisted of three plants. Evaluations were performed at15-day intervals on 30 leaﬂets per tree. Disease incidence was quantiﬁed and infection classiﬁed according to the stages of development andtype of damage. Leaf blight occurred during the entire experimental period; however, disease intensity varied with the resistance level of theclones and the time of year. Clones FX 3864, RRIM 725, RRIM 711, IAC 300 and IAN 873 exhibited the highest resistance to leaf blight.